Tantangan dan Peluang dalam Penerapan Manajemen Persuratan Berbasis Digital - Tiara Lubis; Rizka Amanda Putri; Rheina Sayla; Fikri Hamdi Siregar; Muhammad Yasir Ardiansyah; Tengku Darmansah (Ebisnis Manajemen, 2025)
The development of information and communication technology has changed many aspects of life, including in terms of administration and management of letters. In this digital era, the conventional letter system that uses paper media has gradually shifted to a more efficient digital system. Correspondence management in the digital era refers to the process of managing letters or correspondence by utilizing digital technology to improve efficiency, security, and speed in managing letters. Although correspondence management uses technology that can simplify the process, correspondence management is not free from things that can hinder the process. The purpose of writing this article is to find out what can be challenges or obstacles in managing digital-based correspondence. The results of this study indicate that there are several things that are inhibiting factors in correspondence management and several solutions offered by the author in overcoming these obstacles.